Predictive factors of overall functioning improvement in patients with chronic schizophrenia and schizoaffective disorder treated with paliperidone palmitate and aripiprazole monohydrate. (15th May 2018) - Girardi, Paolo; Del Casale, Antonio; Rapinesi, Chiara; Kotzalidis, Georgios D.; Splendori, Francesca; Verzura, Claudio; Trovini, Giada; Sorice, Serena; Carrus, Dario; Mancinelli, Iginia; Comparelli, Anna; De Filippis, Sergio; et al.
Abstract: Background: Long‐acting injectable (LAI) antipsychotics can improve medication adherence and reduce hospitalisation rates compared with oral treatments. Paliperidone palmitate (PAL) and aripiprazole monohydrate (ARI) LAI treatments were associated with improvements in global functioning in patients with schizophrenia. Objective: The objective of this study was to assess the predictive factors of better overall functioning in patients with chronic schizophrenia and schizoaffective disorder treated with PAL and ARI. Method: Enrolled were 143 (97 males, 46 females, mean age 38.24 years, SD  = 12.65) patients with a diagnosis of schizophrenia or schizoaffective disorder, whom we allocated in two groups (PAL and ARI treatments). We assessed global functioning, amount of oral medications, adherence to oral treatment, and number of hospitalisations before LAI introduction and at assessment time point. Results: Longer treatment time with LAIs ( p  < .001), lower number of oral drugs ( p  < .001), and hospitalisations ( p  = .002) before LAI introduction, and shorter duration of illness ( p  = .038) predicted better Global Assessment of Functioning scores in the whole sample ( R 2  = 0.337). Conclusion: Early administration and longer duration of ARI or PAL treatments could play a significant role in improving global functioning of patients with schizophrenia and schizoaffective disorder. Better improvement in functioning could be achieved with ARI in young individuals with recent illness onset and PAL in patients at risk for recurrent hospitalisations.